RESPONSE OF RHIZOBIUM INOCULATION AND PHOSPHORUS LEVELS ON MUNGBEAN (VIGNA RADIATA) UNDER GUAVA-BASED AGRI-HORTI SYSTEM - S. K. PRASAD; M. K. SINGH; SINGH, JAY (The Bioscan, 2014)
In present investigation an attempt has been made to integration of crops in orchards to meet the fruit and grain demand with sustaining soil health. In this regard, a field experiment was conducted during kharif, 2010 to evaluate the effect of rhizobium inoculations and phosphorus levels on performance of mungbean under guavabased agri-horti system. Among the treatments, rhizobium inoculation + 60 kg P2O5/ha had significant influence on growth and yield attributing characters and consequently the significant increased yield (1011 kg/ha) with rhizobium inoculation(RI) + 60 kg P2O5/ha of mungbean under agri-horti system. The significant positive improvement of nodule number (42/plant) under RI + 60 kg P2O5/ha was recorded which was at par with RI + 80 kg P2O5/ha. The N and P content and uptake were also significantly increased with the treatment Rhizobium inoculation + 60 kg P2O5/ ha. N2-fixation capacity and yield components of mungbean were enhanced by application of phosphorus fertilizer. So, combined application of Rhizobium inoculants along with phosphorous fertilizer was considered to be the suitable combination of increasing mungbean production under agri-horti system.